Variations and estimators for self-similarity parameter of sub-fractional Brownian motion via Malliavin calculus. Issue 7 (3rd April 2017) - Liu, Junfeng; Tang, Donglei; Cang, Yuquan
ABSTRACT: Using multiple stochastic integrals and the Malliavin calculus, we analyze the asymptotic behavior of the adjusted quadratic variation for a sub-fractional Brownian motion. We apply our results to construct strongly consistent statistical estimators for the self-similarity of sub-fractional Brownian motion.